The Entanglements of the Empress: A Re-Examination of the Generation of the Stele of Heir Apparent's Making Transcendents and Its Political Implications. - TANG, Wen (Frontiers of History in China, 2026)
The stele erected on the peak of Goushan Mountain in Yanshi, on the reverse of which Empress Wu wrote and calligraphed the Stele of Heir Apparent's Making Transcendents, possesses an unusual history, with rich political implications underlying each stage in its development, which reflects the inner entanglements of Empress Wu during her later reign. This long process can be divided into three parts. First, it was erected in 699, and most of the contents on its front and reverse were completed at that time. Second, in 700, Empress Wu returned from Songshan Mountain to Luoyang. At this time, the "Miscellaneous Verses on Wandering Transcendents" was inscribed on the reverse and top of the stele. Third, in 706, when Prince Xiang and his officials signed their names. Empress Wu copied down the Stele of Heir Apparent's Making Transcendents during the second lunar month of 699 when visiting the newly completed Temple of Heir Apparent's Making Transcendents. Within two months, she had this stele erected. On the reverse, she recorded her reminiscences of her eldest son, Li Hong, her establishing Li Xian as the Heir Apparent, and the speed at which she subsequently proclaimed her strong support for the Heir Apparent to the court and the entire state. Despite this, the Wu clan, led by Wu Sansi, through forging a connection between Zhang Changzong, Zhang Yizhi, and the Stele of Heir Apparent's Making Transcendents, was thus able to successfully eradicate the political implications of this majestic monument. Empress Wu's "Miscellaneous Verses on Wandering Transcendents" was a product of these machinations. The point in time in which Prince Xiang signed his name was thus exactly when Wu Sansi was framing the five princes. Whether or not Prince Xiang leaving the political center and going to Songshan Mountain is related to this requires further investigation.